20,000 words : - Leslie, Louis A. (McGraw-Hill, 1965)
It may suffice to remind the reader that in most cases we go to the dictionary for spelling or word division rather than for a definition. The omission of most definitions in this volume makes it possible to print the word list in large type, even in so small a book.